Islamic Republic of Iran : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This Selected Issues paper for the Islamic Republic of Iran deals with the analytical considerations relating to the choice of the exchange regime. This issue came to prominence with the exchange rate unification of March 2002. The paper also examines the competitiveness of the non-oil economy, fiscal sustainability, and the labor market of Iran. The paper concludes that a degree of flexibility in the exchange rate is needed at this juncture, given Iran's exposure to oil price shocks, and the desire of the authorities to promote the development of non-oil activities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet